(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Subfamily Clytrinae is poorly investigated till now, especially in non-paleartic fauna. A generic system of this group is also quite unsatisfactory and needs in full revision. In this pubblication we describe Pseudolopha laeta n. gen. n. sp. from Thailand and the following nine new species: Protoclytra (Protoclytra) somaliensis n. sp. from Somalia; Barybaena bryanti n. sp. from Kenya; Barybaena minuta n. sp. from Tanzania; Clytra elgae n. sp. from Ethiopia; Afrophthalma neptunus n. sp. from Kenya; Anisognatha monrosi n. sp. from Tanzania; Anisognatha curlettii n. sp. from Tanzania; Aetheomorpha gressitti n. sp. from China; Smaragdina kalimantani n. sp. from Indonesia. Protoclytra (Protoclytra) rajfrayi (Lefévre, 1877) is redescribed and a new synonymy is recognized: Protoclytra vreuricki Burgeon, 1942 = Protoclytra raffrayi (Lefèvre, 1877). Clythra (Barybaena) lurida Lacordaire, 1848 is designated as generotypus of Barybaena Lacordaire, 1848. Besides a new colour form of Aspidolopha buqueti ssp. bomeensis L. Medvedev are proposed.